Agronomy of tree spices (clove, nutmeg, cinnamon and allspice) - a review - KANDIANNAN, K V PETER, C K THANKAMANI, K SIVARAMAN, K (Journal of Spices and Aromatic Crops, 1994)
Clove (Syzygium aromaticum), nutmeg (Myristica fragrans), cinnamon (Cinnamomum verum) and allspice (Pimenta dioica) are important tree spices and have economic value as ingredients in food, beverages and medicines. Agronomical aspects like nursery practices, selection of site, spacing, planting, manuring, mulching, weeding, irrigation and harvesting are important packages for higher and sustainable yield. The available information on these aspects are reviewed.